2011
DOI: 10.1039/c0cc02225j
|View full text |Cite
|
Sign up to set email alerts
|

Rationally controlled helical organization of a multiple-hydrogen-bonding oligothiophene: guest-induced transition of helical-to-twisted ribbons

Abstract: A cyanuric acid-functionalized quaterthiophene self-aggregates to form helical ribbons which are transformed into twisted ribbons upon complexing with a complementary bismelamine receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…76,82,83 These studies have been followed by other hydrogen bonded systems based on various classes of dyes. [84][85][86][87] In an interesting example, the creation of columnar structures by complex formation of a monochromophoric CA-functionalized perylene bisimide derivative and melamine was explored. 88 Concentration-dependent absorption studies of a 1 : 1 mixture in chloroform showed a cooperative process when the data was fitted to a nucleationelongation model.…”
Section: Strategies To Create Cooperative Systemsmentioning
confidence: 99%
“…76,82,83 These studies have been followed by other hydrogen bonded systems based on various classes of dyes. [84][85][86][87] In an interesting example, the creation of columnar structures by complex formation of a monochromophoric CA-functionalized perylene bisimide derivative and melamine was explored. 88 Concentration-dependent absorption studies of a 1 : 1 mixture in chloroform showed a cooperative process when the data was fitted to a nucleationelongation model.…”
Section: Strategies To Create Cooperative Systemsmentioning
confidence: 99%
“…Irradiation of the xerogel using a laser pulse (λ = 355 nm) resulted in the generation of long-lived charge carriers showing maximum transient conductivities (Φ∑μ) of 1.0 × 10 –4 cm 2 V –1 s –1 for 541 and 0.67 × 10 –4 cm 2 V –1 s –1 for the coassembly. The cyanuric acid functionalized quaterthiophene 542 (Chart ) self-assembled to form helical ribbons which transformed into twisted ribbons upon complexation with a complementary bismelamine receptor B1 (Chart ) . The hierarchical self-organization of the flexible quasi 1D copolymers formed by 542 and DE1 (Chart ) led to helical nanofibers and gels .…”
Section: Oligomeric π-Systems Based Gelsmentioning
confidence: 99%
“… 10 In the case of 3 , the resulting finite stacks of supramolecular polymers twist like amyloid β-fibrils to form helical nanofibers. 13 , 14 In this model, helical nanofibers can grow in their lengths through the elongation of hydrogen-bonded chains and in their thicknesses through the stacking of oligothiophene moieties, respectively. On the other hand, supramolecular polymers of 4 organize into crystalline multilamellar structures ( Fig.…”
Section: Resultsmentioning
confidence: 99%